The Australian Work Exposures Study: Occupational Exposure to Lead and Lead Compounds. - Driscoll, T.; Carey, Renee; Peters, S.; Glass, D.; Benke, G.; Reid, Alison; Fritschi, Lin (2015)
INTRODUCTION: The aims of this study were to produce a population-based estimate of the prevalence of work-related exposure to lead and its compounds, to identify the main circumstances of exposures, and to collect information on the use of workplace control measures designed to decrease those exposures. METHODS: Data came from the Australian Workplace Exposures Study, a nationwide telephone survey which investigated the current prevalence and circumstances of work-related exposure to 38 known or suspected carcinogens, including lead, among Australian workers aged 18-65 years. Using the web-based tool, OccIDEAS, semi-quantitative information was collected about exposures in the current job held by the respondent. Questions were addressed primarily at tasks undertaken rather than about self-reported exposures. RESULTS: A total of 307 (6.1%) of the 4993 included respondents were identified as probably being exposed to lead in the course of their work. Of these, almost all (96%) were male; about half worked in trades and technician-related occupations, and about half worked in the construction industry. The main tasks associated with probable exposures were, in decreasing order: soldering; sanding and burning off paint while painting old houses, ships, or bridges; plumbing work; cleaning up or sifting through the remains of a fire; radiator-repair work; machining metals or alloys containing lead; mining; welding leaded steel; and working at or using indoor firing ranges. Where information on control measures was available, inconsistent use was reported. Applied to the Australian working population, approximately 6.3% [95% confidence interval (CI) = 5.6-7.0] of all workers (i.e. 631000, 95% CI 566000-704000 workers) were estimated to have probable occupational exposure to lead. CONCLUSIONS: Lead remains an important exposure in many different occupational circumstances in Australia and probably other developed countries. This information can be used to support decisions on priorities for intervention and control of occupational exposure to lead and estimates of burden of cancer arising from occupational exposure to lead.